Climate sensitivity and attribution analysis of water resources in China - Youzhu Zhao; Qiuxiang Jiang; Zilong Wang (Ecological Indicators)
Given global climate change and human pressures on water resource systems, assessing the sensitivity of terrestrial water storage (TWS) to climate variables is crucial for addressing water shortages and optimizing management strategies. Previous studies have focused on TWS sensitivity to a single climate variable, such as precipitation or temperature. In contrast, this study examines TWS sensitivity to both, revealing regional variations. Additionally, it explores the influence of key climate and human factors on TWS across different sensitivity categories. Results indicate that TWS in eastern China exhibits high sensitivity to precipitation, while TWS in the central areas and parts of the western border areas is more sensitive to temperature changes. However, only 14.87% of the regions show significant sensitivity to both precipitation and temperature. Further analysis identifies key thresholds in the stability, mean, and standard deviation of precipitation and temperature that drive nonlinear changes in TWS sensitivity, affecting the direction of water storage responses to climate change. Based on sensitivity analysis, TWS responses are categorized into distinct sensitivity categories. Through a partial least squares structural equation model, the study identifies a significant positive effect of climate changes on TWS across all sensitivity categories, while human activities tend to have a negative impact. Vegetation influences vary across different categories. By comprehensively considering the complex interactions among climate, vegetation, and human activities on water storage in China, this research enhances our understanding of the complex response mechanisms of water resource systems to climate change and provides a scientific basis for developing more adaptive and sustainable water resource management strategies.